Investigation of Factors Affecting e-Purchase Decision - Pramudita Faddila``, Syifa; Nurlenawati, Netti; Hendayana, Yana (International Journal of Psychosocial Rehabilitation, 2020)
Information technology that is rapidly developing provides convenience and opportunities for the producers to market their products and for the customers to purchase them online. These conveniences make the online business grows bigger. This research’s aim it to analyze the effects of promotion, price, brand image, and customer trust on fashion product purchase decision online for students of Management Study Program, Universitas Buana Perjuangan Karawang. This research uses analytical descriptive methods. The result of this research shows that partially, the price (P-value=0.007) and customer trust (P-value=0.0005) variables influence the fashion product purchased decision online. Moreover, simultaneously, promotion, price, brand image, and customer trust influence the fashion product purchase decision online (P-value=0.0005). The online business producers are recommended to pay attention to determine the price of products, because, for students, price is the most attractive factor to purchase the fashion products online. The customer trust can be maintained by improving the integrity of producers, e.g. giving the products matching the description that is posted online.